2017
DOI: 10.1093/ofid/ofx089
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic H30 Subclone of Sequence Type 131 (ST131) as the Leading Cause of Multidrug-Resistant Escherichia coli Infections in the United States (2011–2012)

Abstract: SummaryAmong US clinical Escherichia coli isolates from 2011–2012, sequence type 131 (ST131) was even more prevalent (26.4%) than reported previously for 2007 isolates (17%). The ST131-H30 subclone (19.8% prevalence), with its H30Rx subset (6.6%), accounted for most fluoroquinolone, extended-spectrum cephalosporin, and multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 40 publications
10
117
2
2
Order By: Relevance
“…bla CTX-M+TEM was the dominant bla gene type, which is consistent with the results of other studies detecting these genes in ESBL producers from companion animals in China and other counties [11,16,31]. CTX-M-15-producing E. coli of ST131 was not found in the present study, which is regarded as an emerging human pandemic clone [32]. However, ESBL-producing E. coli has been detected in urinary samples of dogs in Europe [12].…”
Section: Discussionsupporting
confidence: 91%
“…bla CTX-M+TEM was the dominant bla gene type, which is consistent with the results of other studies detecting these genes in ESBL producers from companion animals in China and other counties [11,16,31]. CTX-M-15-producing E. coli of ST131 was not found in the present study, which is regarded as an emerging human pandemic clone [32]. However, ESBL-producing E. coli has been detected in urinary samples of dogs in Europe [12].…”
Section: Discussionsupporting
confidence: 91%
“…Avoidance of repeated antimicrobial use, which may select for MDR bacterial strains, is desirable because of the potential risk posed to the individual and in-contact humans and animals. Further intensifying concern is the isolation of successful human-associated clonal lineages including ST131-B2 from the urine of dogs (Pomba et al, 2009;Platell et al, 2010), as such strains have been reported in association with extraintestinal disease in both humans and animals (Nicolas-Chanoine et al, 2008;Blanco et al, 2009;Oteo et al, 2009;Ewers et al, 2010;Johnson et al, 2010;Lee et al, 2010;Blanco et al, 2011;Platell et al, 2011a, c;Rogers et al, 2011;Nebbia et al, 2014;Madigan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Common scenarios for evacuation such as road trauma & combat injuries have high background rates of secondary infection [117].…”
Section: Patientsmentioning
confidence: 99%
“…High rates of infection caused by multi-resistant gram-negative bacilli have been reported in injured military personnel evacuated from Iraq and Afghanistan [114,115]. Some studies estimate bacterial infection complicating 15 to 25% of admissions [116,117]. Etiological investigation of infections has implicated both environmental contamination of field hospitals and frequent nosocomial transmission within the military health system [118,119].…”
Section: Aeromedical Evacuation Of Military Personnelmentioning
confidence: 99%
See 1 more Smart Citation